POLA ASUH ORANG TUA DENGAN PERILAKU SOSIAL SISWA - Adelina Nur Hidayah, H.E Bahruddin (LP2M Universitas Muslim Nusantara Al Washliyah, 2020)
This research aims to know the relation of parenting pattern with the social behavior of students in SMPIT Ar-Rahmah Bogor. The research method is quantitative. This research at september 9th – 19th, 2019. In data analysis techniques using the The sample used is 71 respondents in this study selected by using probability sampling with random sampling technique. Data retrieval techniques in this study using a questionnaire method, to collect parenting data applied by parents with social behavior of students. Technique analyze the data used to test the hypothesis is uji-t after beforehand conducted by a prerequisite test that is test the normalitas. The result of examination of normalitas data use the test correlation can be found between variable x and variable y has coefficient of corralation equal to 0,341 or 0,341 ≥ α = 0,03.when referred to interpretation evidently reside among 0,20 – 0,399. this means hypothesis of zero (Ho) refused, so that mean hypothesis alternative (ha) it’s accepted that pattern of parenting have an effect on to social child ability. The result of the research coducted on 71 respondents found that most parents use authoritarian parenting pattern with active social behavior.